Odpowiedzi

Najlepsza Odpowiedź!
2009-11-03T00:06:05+01:00
Rozwiąż równanie kwadratowe

2x+1/x+3 - x-1/x²-9=x+3/3-x - 4+x/3+x /(x²-9)
(2x+1)(x-3)-(x-1)=-(x+3)(x+3)-(4+x)(x-3)
2x²-6x+x-3-x+1=-x²-6x-9-4x+12-x²+3x
2x²+2x²-6x+6x+4x-3x-2+9-12=0
4x²+x-5=0
Δ=1+80=81, √Δ=9
x₁=-1-9/8=-10/8=-5/4
x₂=-1+9/8=8/8=1
Odp. x₁=-5/4 lub x₂=1
2009-11-03T01:09:50+01:00
Po sprowadzeniu do współnego mianownika i wykonaniu
obliczeń otrzymamy
4*x^2 +x - 5 = 0
delta= 81
pierw. kw. z delty = 9
x1 =[-1-9]/8 = -10/8 = -5/4
x2 =[-1 +9]/8 =8/8 = 1
odp. x1 = -5/4
x2 = 1